Workout at a virtual gym: Surrounding avatar's motion speed and exercise intensity effect on the user's time perception. - Bingcheng Ke; Tzu-Yang Wang; Takaya Yuizono; Hideaki Kanai (PLoS ONE)
This study explored the relationship between surrounding avatars and time perception in a virtual reality (VR) gymnasium. Previous research has highlighted that motion speed and exercise intensity significantly influence time perception. In VR, time perception is shaped by various factors, such as an avatar's embodiment at different levels. However, the specific effects of the surrounding avatar on time perception in a VR gymnasium context remain unclear. Thus, this study focuses on two key attributes of the surrounding avatar: (1) motion speeds and (2) exercise intensity. Participants in a VR gymnasium either rode a stationary bike or sat on one while observing avatars performing exercises in the virtual environment(VE). They were then asked to estimate the duration judgment and the feeling of the passage of time for each task. The results revealed that when the surrounding avatars exercised at a faster motion speed, participants perceived the duration of time as longer and felt that time passed more quickly. Additionally, high-intensity exercise led participants to perceive the passage of time as faster.